Effect of Non-Tariff Measures from Third Countries Towards the Export of Goods from Bulgaria - Antov, Momchil (Research Papers, 2020)
The foreign trade policy of the European Union covers all measures affecting imports and exports of goods that have been introduced in relation to third countries. Similar measures have been introduced in the EU partner countries and they have an impact on the ability of European exporters (including Bulgarian ones) to sell their goods in these markets. The data presented in the article show the negative impact on Bulgarian exports of the non-tariff measures introduced in relation to the EU by other countries around the world.